Hepatoprotective and antioxidant properties of Momordica charantia in cow urine on Streptozotocin-induced diabetic rat (Journal of Laboratory Animal Science, 2024)
The aim of the present study was to investigate the hepatoprotective and antioxidant activity of Momordica charantia in cow urine on streptozotocin-induced diabetic rats. The alcoholic extract of Momordica charantia was administered orally in cow urine at 200 mg/kg body weight to diabetic rats and the results were compared with standard antidiabetic drug, glinbenclamide. The results showed that there was a significant (P
Keywords: Momordica charantia; cow urine; streptozotocin; hepatoprotective; antioxidant